2013
DOI: 10.1002/aic.14080
|View full text |Cite
|
Sign up to set email alerts
|

Convection battery—modeling, insight, and review

Abstract: Porous electrode theory was used to model performance of the convection battery using lithium iron-phosphate chemistry. The model results and underlying equations were able to quantify and extend previous interpretations of laboratory validation studies. These analyses substantiated the following conclusions on the performance of the convection battery: (a) flow in the convection battery can reduce concentration overpotentials by 99.9%, (b) both the ionic and electron conductivities of solid phases can have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…In the separator, as velocity increases dc / dx simultaneously decreases. At high velocities, dc / dx is essentially zero . E + increases by at least two orders of magnitude for each order of magnitude increase in the velocity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the separator, as velocity increases dc / dx simultaneously decreases. At high velocities, dc / dx is essentially zero . E + increases by at least two orders of magnitude for each order of magnitude increase in the velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Table are values specifically measured for the materials of study reported here. Table reports the remaining parameters used to complete the simulation—these values were fit to the data with values provided from literature and Gordon and Suppes for comparison. These optimized values were determined by a variation of the method of least squares, in which the parameters were continually manipulated until the deviation between experimental and model data was minimized.…”
Section: Model Parametersmentioning
confidence: 99%
“…Alternative flow battery systems beyond the conventional dissolved transition metal electrolytes have also been reported in the literature, including lead-based flow batteries with soluble lead [10] and polymer suspensions [11]. Another modified flow battery that has been developed is a convection battery with the electroactive materials fixed and electrolyte flowing to improve the mass 2 transport of ionic species in the electrolyte [12,13]. These reported systems, however, have performance limitations due to maximum practical electrode thicknesses or the inefficient pumping due to high pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have focused on solving problems arising from the activation and ohmic polarizations, while ignoring the issue relating to mass transport. In fact, mass transport is of great significance for battery performance, especially for operations running at high power density and high state of charge ( SoC )/state of discharge ( SoD ) …”
Section: Introductionmentioning
confidence: 99%